City of heavenly fire - Cassandra Clare (London Walker Books, 2014)
Sixth and final book in Cassandra Clare$1 (Bs internationally bestselling Mortal Instruments series about the Shadowhunters.Discover more secrets about the Shadowhunters in the sixth and final brand-new collectable edition of the internationally bestselling Mortal Instruments series. Gorgeous cover illustration by Mila Furstova, the artist who created the album art for Coldplay$1 (Bs Ghost Stories. Darkness has descended on the Shadowhunter world. Clary, Jace, Simon, and their friends band together to fight the greatest evil they have ever faced... Read all the sensational books in The Shadowhunter Chronicles: The Mortal Instruments, The Infernal Devices, Tales from the Shadowhunter Academy, The Bane Chronicles, The Dark Artifices, The Last Hours and The hadowhunter$1 (Bs Codex.s
Keywords: Fiction